Diachronic analysis of biodiversity: Study of a herbarium "reviewed" by Francesco Cupani (1657–1710) at the end of the 17th century. (3rd July 2016) - Costa, R. M. S.; Pavone, P.; Caruso, R.; Pulvirenti, S.
Abstract: The subject of this paper is the study of the pre-Linnaean herbarium with the inventory number "VII F1 Hortus Botanicus Catinensis " belonging to the Department of Biological, Geological and Environmental Sciences (University of Catania). The volume examined comprises 186 pages (originally 190) with 1–9 specimens on each sheet. The herbarium samples mainly include angiosperms (386), but a few taxa belonging to gymnosperms (1) and pteridophytes (4) are also present. Unfortunately, some specimens are partially or entirely damaged or even missing; nonetheless, it has been possible to identify most of them. As far as the nomenclature is concerned, we find two kinds of handwriting (of which only that of Cupani can be identified), numerous corrections and/or integrations of the polylogus and different types of ink that were used. These elements allow us to state that we are speaking of a herbarium which was prepared by an unknown person and reviewed by Cupani.